Recent Progress in Strain Engineering on Van der Waals 2D Materials Tunable Electrical, Electrochemical, Magnetic, and Optical Properties - Qi, Yaping (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 The Authors. Advanced Materials published by Wiley-VCH GmbH.